Linking Europe - The Role of the Swiss Electricity Transmission Grid until 2050 - Ingmar Schlecht; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2014)
The aim of this paper is to evaluate the role of the Swiss electricity transmission system and the planned network extensions in the context of Central European electricity market developments and thereby the Swiss and European energy transitions. In addition, we conduct a sensitivity analysis of delayed grid investments for Swiss and European network projects, respectively. By deriving a quantification of potential costs and system stability impacts due to delayed network investments, we can identify whether the currently observed lag in many energy investments poses a threat to achieving the envisioned energy transitions.
Keywords: L94; 330; Switzerland; energy transition; network extension; investment delay